An evaluation of irrigation water supply infrastructure to improve conveyance efficiency and water availability at Dzindi Irrigation Scheme, Limpopo Province - Van der Stoep, Isobel (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Rural Engineering Technology))--University of Pretoria, 2007.